Extracellular Matrix: Emerging Roles and Potential Therapeutic Targets for Breast Cancer - Zhao, Yunchun; Zheng, Xiaoling; Zheng, Yongquan; Chen, Yue; Fei, Weidong; Wang, Fengmei; Zheng, Caihong (Frontiers in Oncology, 2021)
Increasing evidence shows that the extracellular matrix (ECM) is an important regulator of breast cancer (BC). The ECM comprises of highly variable and dynamic components. Compared with normal breast tissue under homeostasis, the ECM undergoes many changes in composition and organization during BC progression. Induced ECM proteins, including fibrinogen, fibronectin, hyaluronic acid, and matricellular proteins, have been identified as important components of BC metastatic cells in recent years. These proteins play major roles in BC progression, invasion, and metastasis. Importantly, several specific ECM molecules, receptors, and remodeling enzymes are involved in promoting resistance to therapeutic intervention. Additional analysis of these ECM proteins and their downstream signaling pathways may reveal promising therapeutic targets against BC. These potential drug targets may be combined with new nanoparticle technologies. This review summarizes recent advances in functional nanoparticles that target the ECM to treat BC. Accurate nanomaterials may offer a new approach to BC treatment.